EVALUASI SISA MATERIAL PADA PROYEK PEMBANGUNAN JALAN OUTER RINGROAD JEMBATAN MAHULU – JALAN JAKARTA – JALAN M.SAID PROVINSI KALIMANTAN TIMUR - SAN, IH (KURVA S JURNAL MAHASISWA, 2014)
Material is one of the important components in building construction. The use ofmaterials in the field often lead to the rest of the material is quite high, material wasteminimization efforts will help contractors increase profits as much as possible in addition toreduce the influence of the environmental impact.This study was conducted to determine the quantity of waste material, the source and thecausal factors and material management at the project above. Data were obtained through twoways: (1) a questionnaire distributed to field managers, site supervisors, field implementers,foremen, and other office holders are still involved in the projects, (2) field observations.The results showed that the largest quantities of waste material in a row is a pile,aggregate B, mountain stone, sand, soil deposits, the aggregate S, cement, lean concrete, andready mix concrete. Under the category of indirect percentage of residual waste material isgreater than the direct waste, except cement and piles where the majority of the rest of thematerial that occurs in the physical form field so greatly affect the environmental impact and therest of the material happens to be minimized.